Analisis Ramalan Penjualan Iklan Jenis Jingle dan Add Lips Pada PT. Radio Berita Kaltim (Antara News Radio) Samarinda - Heriyanto Heriyanto (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
This study aims to determine which method is most appropriatebetween the Method of Least Squares (Least Square Method) andMethods Semi average (Semi Average Method) are on StandardError Forecasting (SKP) Smallest in the sale of advertising inparticular types of jingles and add lips the period 2010 / 2011.Formulation of the problem in this research is: "Which UsageAmong Least Squares Method of Forecasting Techniques (LeastSquare Method) and Semi Method Average (Semi Average Method)are on Standard Error Forecasting (SKP) Smallest. The hypothesisin this study is: "Straight Line Trend Analysis Appropriate Used ToCalculate forecast for Ad Sales At PT. Radio East Kalimantan(ANTARA News Radio) Samarinda Namely Least Squares Method(Least Square Method). Analysis and hypothesis testing toolsused are Least Squares Method (Least Square Method), MethodSemi average (Semi Average Method), Standard Error Forecasting(SKP) is used to determine which method is most suitable of thetwo methods. Value Standard Error Forecasting (SKP) of thesmallest shows that the forecast drawn closer conformity. Theanalysis showed that the Least Squares Method (Least SquareMethod) is the most appropriate method is used to forecast thetype of jingle advertising sales and add lips as has Standard ErrorForecasting (SKP) Smallest. It is seen from the calculation of thetype of ad sales forecast jingle advertising sales increased asmuch as 94 units with total revenues Rp28.200.000, - and StandardErrors Forecasting (SKP) 2.08. Ad sales types lips add as many as101 units with a total revenue Rp48.480.000, - and Standard ErrorsForecasting (SKP) 0.87. In calculating the average Semi method(Semi Average Method) advertising jingle types of 222 units with atotal revenue Rp 66.600.000, - and Standard Errors Forecasting(SKP) 3.85. Ad sales types lips add a total of 106 units with a totalrevenue Rp50.880.000, - and Standard Errors Forecasting (SKP)1.08. These findings indicate that the research hypothesis isaccepted.